Penerapan IoT dalam Sistem Otomatisasi Kontrol Suhu, Kelembaban, dan Tingkat Keasaman Hidroponik - Mohammad Ridwan; Kristine Monita Sari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The growing population in Indonesia and the narrowing of agricultural land have the potential to cause a decline in agricultural production and scarcity of food sources in the future. Hydroponics is a pattern of cultivation with water media with important parameters including the quantity of nutrients provided, the level of acidity and the availability of water that functions as a nutrient solvent medium for plants. Difficulty in monitoring and not having much time to control these parameters is a concentration that must be investigated. This study aims to develop a monitoring and control system for hydroponic plants automatically based on the Internet of Things (IOT). The research was carried out by modeling a control device consisting of a microcontroller, temperature sensor, pH sensor, and also a wifi device that was integrated with the Blink Library as a receiving system for parameter monitoring results. The test uses the blackbox method to test the performance of the system which gets the results of the component automation test (WLS and Relay) with 100% functioning, while the temperature and humidity test has an error value of 4.81% and 5.37% with DHT11, and the test pH (acidity level) in 6.08 buffer solution obtained an average result of 6.68 with an error value of 1.8%. Keywords: Internet of Things, hydroponics, hydroponic automation, pH sensor, temperature humidity sensor